Science learning with a contextual approach based on local wisdom for to enhance elementary school students achievement - Rahman Rahman; Shirly Rizki Kusumaningrum; Mardhatillah Mardhatillah (Universitas Papua, 2026)
Elementary science learning requires instructional approaches that enable students to connect scientific concepts with authentic experiences that are meaningful within their own cultural and environmental contexts. However, science instruction in many elementary classrooms remains predominantly teacher-centered, limiting students’ conceptual understanding and meaningful engagement with science. This study aimed to compare the effectiveness of contextual teaching and learning (CTL) integrated with local wisdom and direct instruction in improving elementary students’ science learning achievement. A quasi-experimental study employing a posttest-only control group design was conducted with 60 fifth-grade students from SDN 020 Tana Tidung, Indonesia. The experimental group received CTL integrated with local wisdom, whereas the control group was taught using direct instruction. Students’ science learning achievement was measured using a 25-item multiple-choice test that demonstrated satisfactory content validity (Aiken’s V = 0.83) and internal consistency reliability (Cronbach’s α = 0.87). Data were analyzed using an independent samples t-test following normality and homogeneity assumption testing. The results showed that the experimental group achieved a higher mean posttest score (82.00) than the control group (74.50), and the difference was statistically significant (p < .05). These findings indicate that integrating local wisdom into CTL provides a more meaningful learning environment by connecting scientific concepts with students’ everyday cultural and environmental experiences. This study contributes to the growing evidence supporting culturally responsive science education and suggests that integrating local wisdom into contextual learning can enhance elementary students’ science achievement.